Standard of Four-Star Hotel Toilet Hygiene in Palembang - Zulkifli Harahap; Muhammad Taslim (Journal Hotspot, 2021)
Since hosting the Sea Games and Asean Games, Palembang has become one of the tourist destinations in Indonesia. To support its role as a tourist destination, the existence of accommodation is clearly needed. The study was conducted to find out the standards of public toilet hygiene, which is one of the most important parts of a hotel. There are five hotels that are used as qualitative research objects. Data is taken through interviews, surveys and literature studies. The results obtained state that the standard in each hotel is perfect with a value of one hundred each. The advice given is that the cleanliness that has been achieved should be maintained.